(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Sonography is a type of medical imaging test that uses high-frequency sound waves to create pictures of different internal parts of the body, like the uterus, heart, intestines, and other organs.1 Sonography uses ultrasound technology to create an image known as a sonogram. This technology is one of the most common imaging tests used to diagnose and treat medical conditions.